Thyroid Dysfunction in Patients with Type 2 Diabetes Mellitus attending Medical Outpatient/Inpatient Departments at a Tertiary Care Hospital - Nirmal Ghimire; Krishna Chandra Devkota; Dinesh Koirala; Susmita Gyawali (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Diabetes mellitus and thyroid dysfunction are the two most common endocrine disorders in clinical practice. The unrecognized thyroid dysfunction may adversely affect the metabolic control and add more risk to an already predisposing scenario for cardiovascular diseases. The objective was to find out the spectrum of thyroid dysfunction in patients of type 2 diabetes mellitus. Materials and Methods: Seventy patients (40 female and 30 male) of age more than 30 years with type 2 diabetes mellitus were evaluated for one year visiting Nepal Medical College and Teaching Hospital. All the patients were evaluated for thyroid dysfunction by testing thyroid function test. The correlation of prevalence of thyroid disorder with gender distribution, age distribution, HbA1c, duration of diabetes was evaluated. The observations and interpretations were recorded and results obtained were statistically analyzed. Results: There was a high prevalence (27.1%) of thyroid disorders in patients of type 2 diabetes mellitus. Among all, the most common was subclinical hypothyroidism (20.0%) which was further found to be more in females (30.0%) and elderly patients (37.0%). Duration of diabetes had positive association with the incidence of thyroid disorders (P value 0.003). Conclusion: Findings of this study suggests that thyroid disorders were commonly associated with diabetes mellitus among which subclinical hypothyroidism being the commonest. Moreover, thyroid disorders were more common in females and elderly population.